Human Rights Based Approaches to Development Concepts, Evidence, and Policy - Gauri, Varun; Gloppen, Siri (2012)
This paper assesses the benefits, risks, and limitations of human rights based approaches to development, which can be catalogued on the basis of the institutional mechanisms they rely on: global compliance based on international and regional treaties; the policies and programming of donors and executive agencies; rights talk; and legal mobilization. The paper briefly reviews the politics of the first three kinds of human rights based approaches before examining constitutionally based legal mobilization for social and economic rights in greater detail. Litigation for social and economic rights is increasing in frequency and scope in several countries, and exhibits appealing attributes, such as inclusiveness and deliberative quality. Still, there are potential problems with this form of human rights based mobilization, including middle class capture, the potential counter-majoritarianism of courts, and difficulties in compliance. The conclusion summarizes what is known, and what remains to be studied, regarding human rights based approaches to development.